Vernakalant for the Conversion of Atrial Fibrillation: The New Kid On the Block? - Conde, Diego (Ann Noninvasive Electrocardiol, 2014)
Conversion of recent onset atrial fibrillation (AF) to sinus rhythm with antiarrhythmic drugs reduces the risk of hemodynamic instability, hospitalizations, and atrial remodeling seen with persistent AF. This is the main reason for pharmacological or electrical cardioversion to be considered first line of treatment for recent onset AF. Is there a role for new antiarrhythmic drugs in the conversion of AF as the first approach to a rhythm‐control strategy? Vernakalant is a novel and relativity atrial selective drug which inhibits atrial‐selective K(+) currents, with only a small inhibitory effect on the rapidly activating delayed rectifier K(+) current (IKr) in the ventricle. In this brief Review, we tell the journey of vernakalant to become an attractive alternative to achieve pharmacological cardioversion of AF.